Four flavonoids from Hedyotis nigricans - Tuyen, Pham Nguyen Kim; Duy, Le Hoang; Phung, Nguyen Kim Phi (Vietnam Journal of Chemistry, 2012)
Four flavonoids, 5-hydroxyflavone (1), 5,7-dihydroxyflavone (2), 5,7,3’,4’-tetrahydroxyflavone (3), and 5,7-dihydroxy-4’-methoxyisoflavone (4) were isolated from the ethyl acetate extract of whole plant of Hedyotis nigricans. These compounds were previously also isolated from other plants. However, they were the first time known to be present in Hedyotis genus from H. nigricans. The present paper reports the spectroscopic analyses which lead to the elucidation of their structures.